Adverse Allergic Reaction to Intrathecally Administered Technetium-99m Diethylenetriamine Pentaacetate: A Case Report - Nair, Ahalya; Poolpandian, Guneshwaran; Dhayalan, Kabilash; Saibaba, Jayaram (World Journal of Nuclear Medicine, 2023)
Intrathecal administration of radiopharmaceuticals is an infrequently performed procedure in most nuclear medicine facilities. It is possible that adverse allergic reactions following the intrathecal administration of radiopharmaceuticals often go unreported. Here we present a case of spontaneous cerebrospinal fluid rhinorrhea with recurrent bacterial meningitis, who underwent radionuclide cisternography for localization of the site of leak and developed an adverse allergic reaction following the intrathecal administration of technetium-99m diethylenetriamine pentaacetate that resolved with appropriate treatment. Imaging, however, could be carried out to our satisfaction and the allergic reaction did not interfere with, or result in discontinuation of the scan procedure.
Keywords: adverse allergic reaction; CSF rhinorrhea; intrathecal route; radionuclide cisternography; 99mTc DTPA